2020
DOI: 10.1111/bjd.19049
|View full text |Cite
|
Sign up to set email alerts
|

Habitual scratching amplifies and perpetuates atopic dermatitis

Abstract: Linked Article: Gouin and Misery. Br J Dermatol 2020; 182:14–15.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Brain imaging research has shown atypical brain activation patterns in eczema patients a er pruritic stimulation, suggesting central sensitisation (Misery 2021). Techniques such as habit reversal work on the notion that scratching can become unconscious and widespread beyond the itch itself (Staughton 2020). Such techniques teach patients how to use di erent, less harmful, behaviours where the itch perseveres.…”
Section: Psychological Interventionsmentioning
confidence: 99%
“…Brain imaging research has shown atypical brain activation patterns in eczema patients a er pruritic stimulation, suggesting central sensitisation (Misery 2021). Techniques such as habit reversal work on the notion that scratching can become unconscious and widespread beyond the itch itself (Staughton 2020). Such techniques teach patients how to use di erent, less harmful, behaviours where the itch perseveres.…”
Section: Psychological Interventionsmentioning
confidence: 99%